2023
DOI: 10.1590/fst.99922
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of biscuits with olive pomace

Abstract: This work developed biscuits with the partial substitution of wheat flour with olive pomace flour (OPF). The wheat flour contents substituted by OPF in the biscuits were 0%, 10%, and 20%. The effects of the flour on the chemical composition, lipid profile, and sensory aspects of the reformulated biscuits were evaluated. The data showed that the OPF has a high concentration of dietary fiber (43.75%) and 27.70% lipids. The biscuit with 10% of the wheat flour replaced by OPF has 4.29% of total dietary fiber and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…Caponio et al [41] reported a similar dry matter and protein content for FD-OP, whereas significant differences were seen in the total dietary fibre (TDF)/DM, for which they reported 20.10% compared with the 61.1% (Bosana) to 66.7% (Semidana) observed in the present study. Other studies report TDF levels closer to those found here, such as 43.75% [51], 54.5% [52], and 57.96% [53].…”
Section: Characterization Of Olive Pomacesupporting
confidence: 89%
“…Caponio et al [41] reported a similar dry matter and protein content for FD-OP, whereas significant differences were seen in the total dietary fibre (TDF)/DM, for which they reported 20.10% compared with the 61.1% (Bosana) to 66.7% (Semidana) observed in the present study. Other studies report TDF levels closer to those found here, such as 43.75% [51], 54.5% [52], and 57.96% [53].…”
Section: Characterization Of Olive Pomacesupporting
confidence: 89%
“…Even though the thermoxidative stability of OPO has been recently investigated at frying conditions [9,10], very little is known about its oxidative changes when used as an ingredient in bakery foods. While olive pomace, defatted or not, has been employed as a partial flour substitute in a variety of baked products, including biscuits [11,12], bread [13] and breadsticks [14], only a bibliographic precedent of the use of OPO in baked foods has been found. This is the work by Caponio and co-workers [15], who studied OPO as a reference refined oil to evaluate the potential use of extra virgin olive oil (EVOO) as an ingredient of "taralli", which is a typical Italian savoury product rich in fat.…”
Section: Introductionmentioning
confidence: 99%